Theoretical analysis of tangent hyperbolic nanoparticles with combined electrical MHD, activation energy and Wu's slip features: a mathematical model. (20th September 2019) - Khan, Sami Ullah; Waqas, H; Shehzad, S A; Imran, M
Abstract: Current study deals with the rheology of non-Newtonian material over moving surface by utilizing the electrical, magnetohydrodynamics and activation energy effects. A famous tangent hyperbolic viscoelastic fluid model has been used in presence of nanoparticles which may extremely useful to enhance the transportation phenomenon. The second order slip effects (Wu's slip) are also entertained in the boundary conditions. Further, the energy equation occupied the nonlinear thermal radiation while the activation energy expression is carried out in the concentration equation. The highly nonlinear boundary value problem is metamorphosed into ordinary differential equations by means of the suitable variables. These transmuted equations results the self-similar solution which is computed numerically by shooting technique. First, the reported solution is justified after comparing with available resources and detail graphical analysis have been executed for parameters like Weissenberg number W e, mixed convection buoyancy parameters G r, G c, the power law index n, thermophoresis N t, Brownian constraint N b and slip parameters γ, δ . Further, the impact of suggested parameters on local Nusselt number and Sherwood number is determined in tabular form. It is found that the slip parameters resulted the weaker momentum boundary layer. The nanoparticles temperature is enhanced by the increasing values of thermophoresis and Brownian motion parameters, Weissenberg and thermal Biot numbers. Further, the convection parameters decrease the nanoparticles concentration while presence of activation energy slightly boosts up the nanoparticles concentration.